Effect of optimization methods on Hansen solubility ellipsoids. Issue 12 (21st November 2016) - Weng, Ming
ABSTRACT: In Hansen solubility parameters (HSPs) space, the solubility region of a solute is modeled as an axis‐aligned ellipsoid, of which Hansen sphere is a special case. The solubility ellipsoids of six materials are determined by the data fit function proposed by Hansen and a new objective function, both solved by a hybrid global‐local search algorithm. From the calculated and reported results, the validity and applicability of four types of currently used optimization methods are analyzed, the findings of and reasons for disputable problems are elucidated. The results reveal that the objective function defined for finding a smallest ellipsoid enclosing all good solvents and having the lowest number of outliers leads to reliable results, thereby has advantages over the methods based on the data fit function. The global convergence and capability of locating multiple optima are essential for a search algorithm used for determining solubility regions. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44621. Abstract :